Crescimento e acúmulo de nitrogênio e potássio pelo melão pele de sapo fertirrigado - Temóteo, Amansleone da S. [UNESP]; de Medeiros, José Francismar [UNESP]; Dutra, Indalécio [UNESP]; de Oliveira, Francisco de Assis [UNESP] (My University, 2010)
With the objective of obtaining dry matter curves, and nitrogen and potassium accumulation in Piel de Sapo melon (Cucumis melo L.) hybrid Sancho, an experiment was conducted in Mossoró - RN in a randomized blocks design with three repetitions. Treatments consisted of doses in kg ha-1 of nitrogen: 0, 91, 140 and 184 and potassium: 0, 174, 260 and 346; which were applied by fertigation in depths of 281, 349 and 423mm. Stems, leaves and fruits were harvested 5 times at 28 to 70 days after transplantation, in intervals of 10 days for analyses of aerial dry matter, nitrogen, and potassium accumulation. Doses higher than 140 and 260 kg ha-1 of N and K respectively, did not induce greater accumulation of these nutrients increasing levels throughout the plant cycle. Nitrogen doses of 91 and 140 kg ha-1, potassium doses of 174 and 260 kg ha-1 as well as depth of 348mm provided higher accumulation of potassium in the plant.

Com o objetivo de obter curvas de massa seca e de acúmulo de nitrogênio e potássio pelo melão Pele-de-Sapo (Cucumis melo L.) híbrido Sancho, sob fertirrigação e diferentes lâminas de irrigação, conduziu-se um experimento em Mossoró-RN, num delineamento experimental em blocos casualizados com três repetições. Os tratamentos consistiram de doses, em kg ha-1, de nitrogênio: 0, 91, 140 e 184 e de potássio: 0, 174, 260 e 346 aplicadas via fertirrigação sob três lâminas de irrigação: 281, 349 e 423 mm. Realizou-se cinco coletas da parte aérea das plantas (caule, folha e fruto) a partir dos 28 até 70 dias após transplantio, em intervalos de 10 dias, para determinações da massa seca da parte aérea e acúmulo de N e K. Doses superiores a 140 e 260 kg ha-1 de N e K (utilizadas pelos produtores da região) respectivamente não promoveram aumento no acúmulo de fitomassa seca total. As doses crescentes de nitrogênio garantiram os maiores acúmulos deste nutriente ao longo do ciclo da planta e as doses de N de 91 e de 140 kg ha-1, e de K de 174 e de 260 kg ha-1 e a lâmina de 349 mm proporcionaram maior acúmulo de potássio na planta.
Growth and absorption of N and K by fertigated frog skin, melon
Keywords: Cucumis melo L.; Irrigation depths; Mineral nutrition; absorption; accumulation rate; experimental design; fruit; growth rate; irrigation system; nitrogen; potassium; Anura; Cucumis; Cucumis melo